The Presentation Form of the song "Toba Dream: Theme Song" by the Marture Music Group in the Batak Toba Ulaon Unjuk Wedding Ceremony - Nandita Aurel Manurung (Repertoar, 2026)
This study aims to describe the components of the presentation and analyze the structure of the song "Toba Dream: Theme Song" during the ulaon unjuk manomu-nomu stage of a Batak Toba wedding. This study uses a descriptive qualitative method through non-participant observation, structured interviews, and documentation. Data analysis techniques included data collection, data observation and presentation, and data conclusion. The results of this study show that the presentation form of the song "Toba Dream: Theme Song" in the Ulaon Unjuk procession has components that support the performance, namely musicians, musical instruments, songs presented, fashion, stage setting, sound system, audience, as well as the time and place of the event. The presentation form of the song "Toba Dream: Theme Song' during the initial procession of ulaon unjuk manomu-nomu, performed by the Marture music group, was presented in the form of Gondang music with a presentation structure divided into Intro, verse I, chorus I, verse II, chorus II, verse III, chorus III, verse IV, interlude, chorus IV, and ending. From the results of this analysis, it can be seen that Gondang music serves as entertainment and accompanying music, as well as providing structure and rhythm for the entire wedding ceremony.